Perspectives on antimicrobial resistance in livestock and livestock products in ASEAN countries - Archawakulathep, Amornthep; Chung, Ta Thi Kim; Meunsene, Dethaloun; Handijatno, Didik; Abu Hassim, Hasliza; Rovira, Hope R. G.; Myint, Khin Sandar; Baldrias, Loinda R.; Sothy, Meas; Aung, Min; Wahyu, Nenny H.; Chea, Rortana; et al. (Chulalongkorn University, 2014)
Antimicrobial resistance (AMR) in bacteria, particularly in foodborne pathogens, has increasingly become apparent in most parts of the world including ASEAN countries, creating great impact on economy, human and animal health and international food trade. The tendency of bacterial pathogens to become multidrug resistant (MDR) is the most serious concern in AMR. The ASEAN Economic Community (AEC) will be fully established in 2015 and ASEAN cooperation has acknowledged the significance of food safety, of which AMR is one of the major concerns. There is a need for all ASEAN nations to harmonize its AMR monitoring and surveillance programmes in order to strengthen the control and institute prevention strategies in the region. Currently, public health systems dealing with monitoring and control in ASEAN countries are still highly diverse and require a unifying action. National monitoring and control programmes for AMR have not been successfully established in most ASEAN countries and a regional-cooperative programme has yet to be set in place. Therefore, a review of current AMR situations in ASEAN member states shall be useful for future development and establishment of monitoring and control programmes within the region.